Evaluation of new forage legume varieties for registration and dissemination in Vietnam - Tran, Ngoc Thi Bich; Bui, Viet Phong; Ngo, Dinh Tan; Than, Minh Hoang; Dao Thu, Hang Thi; Atieno, Mary; Duncan, Alan; Peters, Michael (2024)
Vietnam's livestock sector comprises over 8.57 million cattle and buffaloes, including 6.33 million cattle and 2.23 million buffaloes. Forage biomass, accounting for about 60-85% of the total feed intake of ruminants, is in high demand. However, during the dry season, natural and cultivated grass meet only 35-57% of the forage requirements, leading to critical feed shortages. These deficits, coupled with harsh winters result in the deaths of thousands of cattle annually in the Northern mountainous provinces. Addressing this challenge necessitates identifying and enhancing the utilization of high-quality, alternative feed sources. This study aims to evaluate the adaptation and performance of new legume forage varieties to mitigate forage scarcity in Vietnam. This study evaluated five forage legume varieties including Crotalaria juncea, Crotalaria ochroleuca, Lablab purpureus, Clitoria ternatea and Mucuna pruriens L. as a local check. The study conducted at the Ba Vi Cattle and Forage Research Center (BCFRC) in Hanoi aimed to assess adaptation, growth, and biomass yield of these varieties under both wet and dry seasons, as a prerequisite for introducing new materials into the country for eventual registration and dissemination. The results showed that C. juncea exhibited rapid growth and high yields within two months, while C. ochroleuca had a slower growth rate but outperformed others in fresh biomass yield at harvest. Lablab demonstrated comparable growth to native legumes after the first month, whereas C. ternatea faced challenges due to poor germination and weed competition. The findings underline the potential of high-quality forage legumes to adapt to Vietnam’s agroecology and mitigate forage shortages for livestock. To ensure wider adoption, further on-farm trials across various agro-ecological zones are recommended to validate these results. This study offers promising solutions for enhancing livestock productivity and resilience in Vietnam's forage-scarce regions.